2020
DOI: 10.3390/genes11050530
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Atlantic Distribution and Introgression as Inferred from Single Nucleotide Polymorphism: Mussels Mytilus and Environmental Factors

Abstract: Large-scale climate changes influence the geographic distribution of biodiversity. Many taxa have been reported to extend or reduce their geographic range, move poleward or displace other species. However, for closely related species that can hybridize in the natural environment, displacement is not the only effect of changes of environmental variables. Another option is subtler, hidden expansion, which can be found using genetic methods only. The marine blue mussels Mytilus are known to change their geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 121 publications
2
39
0
Order By: Relevance
“…We have shown that this population is differentiated from both American, and South-European M. edulis, and appears as intermediate in the PCA ( Figure S2), Structure (Figures 2 and S5) and hybrid index analyses ( Figure 5). This observation previously made in Simon et al (2020), has recently been confirmed by Wenne et al (2020). Given its presence as the parental M. edulis population in the Øresund hybrid zone, and the complete absence of American ancestry in the Netherlands, the border between Southern and Northern European M. edulis probably falls somewhere near to the Danish coast (see also the previously observed differences between the North Sea and populations North of the Kattegat region; Stuckas, Stoof, Quesada, and Tiedemann, 2009).…”
Section: The Timing and Context Of Introgressionssupporting
confidence: 61%
See 1 more Smart Citation
“…We have shown that this population is differentiated from both American, and South-European M. edulis, and appears as intermediate in the PCA ( Figure S2), Structure (Figures 2 and S5) and hybrid index analyses ( Figure 5). This observation previously made in Simon et al (2020), has recently been confirmed by Wenne et al (2020). Given its presence as the parental M. edulis population in the Øresund hybrid zone, and the complete absence of American ancestry in the Netherlands, the border between Southern and Northern European M. edulis probably falls somewhere near to the Danish coast (see also the previously observed differences between the North Sea and populations North of the Kattegat region; Stuckas, Stoof, Quesada, and Tiedemann, 2009).…”
Section: The Timing and Context Of Introgressionssupporting
confidence: 61%
“…(2020), has recently been confirmed by Wenne et al. (2020). Given its presence as the parental M. edulis population in the Øresund hybrid zone, and the complete absence of American ancestry in the Netherlands, the border between Southern and Northern European M. edulis probably falls somewhere near to the Danish coast (see also the previously observed differences between the North Sea and populations North of the Kattegat region; Bierne et al., 2003; Stuckas et al., 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Molecular identification was not attempted here, but could help resolve some of these taxonomic uncertainties in future work, as has been done for Mytilus spp. (Wenne et al, 2020). Similarly, nematodes were identified only to the phylum level, but did contribute significantly to the observed differences in assemblages between the Lusitanian and Lusitanian-Boreal regions.…”
Section: Biogeographic Regionsmentioning
confidence: 84%
“…However, due to the uncertainty regarding the morphological distinction at the species level between Mytilus edulis and Mytilus galloprovincialis, particularly at the juvenile stage (Jansen et al, 2007) and because hybridization occurs between the two (Daguin et al, 2001), all specimens sampled in the hybridization area (UK1, UK4, FR1, FR2, FR3, and FR4) were considered as Mytilus spp. (Wenne et al, 2020). All specimens are stored in the Laboratory of Coastal Benthic Ecology's collections at Ifremer (Plouzané, France).…”
Section: Study Area and Sampling Methodsmentioning
confidence: 99%
“…galloprovincialis and M. edulis/Mytilus trossulus, although M. edulis is so far the most abundant species (Mathiesen et al 2017;Węsławski and Kotwicki 2018). A recent study indicated that mussels (M. edulis) found on floating debris around Svalbard were hybrids of boreal and warm temperate taxa, some with genetic structure resembling populations in the UK, Iceland, and western mainland Europe (Wenne et al 2020). This shows the complex interpretation of origin that may also account for other NIS.…”
Section: Oithona Similusmentioning
confidence: 99%